2018
DOI: 10.1007/s00586-018-5577-1
|View full text |Cite
|
Sign up to set email alerts
|

Axial plane dissimilarities of two identical Lenke-type 6C scoliosis cases visualized and analyzed by vertebral vectors

Abstract: Vertebral vectors allow the evolution of scoliosis curve projections in the horizontal plane before and after surgical treatment, along with representation of the entire spine. The top view in the horizontal plane is essential to completely evaluate the scoliosis curves, because, despite the similar representations in the frontal and sagittal planes, the occurrence of scoliosis in the horizontal plane can be completely different. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…The explicit advantage of using VV is the feasibility of displaying the curves in the axial plane. Previous studies have suggested that the curves classified into the same group have different axial plane appearances that are not apparent in single planar radiographic assessments and may necessitate a different surgical strategy [16,17]. Our finding confirms this hypothesis since during the K-means cluster analysis, we distinguished eight different axial plane curve clusters from which three were found in the group with curves < 40°, and five in the group with curves > 40°.…”
Section: Discussionsupporting
confidence: 87%
“…The explicit advantage of using VV is the feasibility of displaying the curves in the axial plane. Previous studies have suggested that the curves classified into the same group have different axial plane appearances that are not apparent in single planar radiographic assessments and may necessitate a different surgical strategy [16,17]. Our finding confirms this hypothesis since during the K-means cluster analysis, we distinguished eight different axial plane curve clusters from which three were found in the group with curves < 40°, and five in the group with curves > 40°.…”
Section: Discussionsupporting
confidence: 87%